Gagasan Penguatan Tugas dan Wewenang Bidang Intelijen Kejaksaan Tinggi Riau Dikaitkan dengan Penggunaan Sarana Non Penal dalam Pencegahan Tindak Pidana Korupsi - Adhy, Mochamad Fitri (Melayunesia Law, 2019)
Based on data on the amount of corruption in the Riau Attorney General's jurisdiction compared to the number of counseling activities and legal information in order to prevent corruption, the role of intelligence in the Riau High Prosecutor's Office in the prevention of corruption is still not effective. The type of this research is sociological legal research. While judging by its nature, this research is descriptive. Obstacles in the implementation of the tasks and authority of the Riau Prosecutor's Office intelligence field are associated with the use of non-penal facilities in the prevention of corruption, are derivative rules and / or implementing rules / norms against the prevention of corruption non-reasoning is still very weak and there are regulations that prevent the prosecutor's intelligence in prevention of criminal acts of corruption, sectoral egos that do not support each other, prosecutors work together to make fraud in order to get personal benefits, low facilities or facilities, limited budget, and the public considers the prosecutor to play or selectively eradicate corruption. This happened because on another occasion the Prosecutor's Office carried out the prosecution in a similar legal event. Corruption behavior is still rooted in the old culture. The idea of strengthening the tasks and authority of the Riau Prosecutor's Office of intelligence is associated with the use of non-penal facilities in preventing corruption, eliminating weak rules and hindering the implementation of prosecutors' duties, eliminating sectoral egos, increasing workspace facilities and increasing the quantity and quality of intelligence tools, influence people's views on crime and punishment through mass media, and eliminate corrupt behavior that is still rooted in the old culture.